Ready or not? Observations from a long-standing community engagement advisory board about investigator competencies for community-engaged research - Matthews, Alicia K. (J Clin Transl Sci, 2018)
Preparing investigators to competently conduct community-engaged research is critical to achieving Clinical and Translational Science Award (CTSA) program goals. The purpose of this study is to describe the perspectives of members of a long-standing community engagement advisory board (CEAB) on investigators’ readiness to engage communities and indicators of investigator competence in community-engaged research, in order to suggest core competencies to guide the development of CTSA-sponsored educational programs. Two 90-minute focus groups were conducted with a subset of members of a CEAB (n=19) affiliated with the Center for Clinical and Translational Science at the University of Illinois at Chicago. CEAB members identified a range of investigator skills and practices that demonstrate readiness to engage in community-engaged research. Eight competencies were identified that should be incorporated in providing education to enhance the readiness and competency of CTSA-affiliated researchers planning to engage communities in research. CEAB observations demonstrate the necessity of developing competency-based educational programs that prepare clinical and translational scientists at all levels for the important work of community-engaged research.